On motivic and arithmetic refinements of Donaldson-Thomas invariants - Espreafico, Felipe; Walcher, Johannes (Communications in number theory and physics, 2024)
International Press of Boston - publishers of scholarly mathematical and scientific journals and books
Gesehen am 16.09.2024